God's Chinese son : the Taiping Heavenly Kingdom of Hong Xiuquan - Spence, Jonathan D. (New York, W.W. Norton and Company, 1996)
It is 1837 when Hong ascends to Heaven. While there, he is charged by God, his Heavenly Father - attired in black dragon robe and high-brimmed hat, his mouth almost hidden by his luxuriant golden beard - to slay the demon devils who are leading the people on earth astray. Their leader is Yan Luo, king of hell, the Dragon Demon of the Eastern Sea. Hong does battle in Heaven, armed by his father with sword and seal, aided by his elder brother, Jesus. Returned to his home village in south China, he resolves to carry on the struggle against the evil polluting humanity. He knows himself to be the younger brother of Jesus Christ, God's Chinese son
The Taiping uprising, led by Hong Xiuquan, was a massive millennial movement that, in its violent rise and fall between 1845 and 1864, cost at least twenty million Chinese their lives. In the course of this struggle the Taiping succeeded in overturning the authority of the ruling Qing dynasty throughout a massive territory in southern China. This the Taiping ruled as their Heavenly Kingdom from their seat in Nanjing for eleven years, until they were overcome in an apocalypse wrought by Qing and Western forces, the Book of Revelation become history
In this master work of the historian's art, Jonathan Spence creates a history of intimate detail and grand scale. We enter the fevered dream world of Hong Xiuquan as he meets his Heavenly family; we see the torments awaiting earthly sinners in King Yan Luo's hell; we feel the anxieties of Westerners living circumscribed lives on the edges of a China they do not understand. This is a China of vast instability, ruled by a dynasty in decline, beset by pirates and bandits in areas beyond the government's reach, pressed by Western traders to embrace opium, Western missionaries the word of God, and arms dealers the new weapons of the industrial revolution. Hong's movement ignites this volatile situation, and Spence captures the result on a breathtaking canvas of clashing armies, daring strategic thrusts, and protracted, deadly sieges. It is a story of historical power with striking resonances today
1. Walls -- 2. The word -- 3. Home ground -- 4. Sky war -- 5. The key -- 6. Wandering -- 7. The base -- 8. Judgments -- 9. Assembling -- 10. Earth war -- 11. The first city -- 12. The hunt -- 13. The earthly paradise -- 14. Three ships -- 15. The split -- 16. The killing -- 17. Family circles -- 18. The wrong man -- 19. New worlds -- 20. Priest-king -- 21. Snowfall -- 22. Partings
Includes bibliographical references (pages 373-388) and index
Keywords: Hong, Xiuquan, -- 1814-1864.; China -- History -- Taiping Rebellion, 1850-1864.; China -- Historia -- Taiping Rebelión de, 1850 1864; History